The Comparison of Communication Skills of Istanbul Gelisim University Physical Education and Sports School Students According to their Departments - Göksu, Tekmil Sezen; Tazegül, Ünsal (Journal of Sports Research, 2017)
The aim of this research was to compare the levels of communication skills of students from the departments of Recreation, Coaching, Sport Management and Sport and Exercise Science of the School of Physical Education and Sports at Istanbul Gelişim University. The Communication Skills Evaluation Scale was used as data collection tool. Portable IBM SPSS Statistics v20 software package was also used to analyze the obtained data. After the data were examined for normal distribution and homogeneity of variance, it was decided to use the parametric test method. The descriptive analysis and one-way Anova analysis which was used to determine the difference between two variances and Tukey’s test were also used to compare the variables among themselves. At the end of the study, it was determined that the students from the department of Recreation Department have a higher level for communication skills than the students from the other departments.